(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Mieke Bal (Maria Gertrudis) is a well known Dutch theorist, artist, literary critic, filmmaker and video artist. She occupied numerous academic positions throughout her life and in the recent times, she is a Professor of Theory and Literature in the Amsterdam University. Her book, Narratology: Introduction to the Theory of Narrative, was printed many times and was translated into English by Christine Van Boheemen. The first edition was printed and published in Canada, Toronto in 1980 and in 1999 the second edition was released with new forward. In her book, Bal gives a deep insight to the basic elements of the narrative from a structural standpoint. In a very systematic way, she lies down the bases of the narrative constructions with a lucid attention to the shared constituents. Naming these constituents of the narrative go accurately with the function. In fact, this book has three main sections with introduction and afterword. The first section is tackling the text in terms of Wording, while the second section is shedding light on the Aspects of the story, as far as the third section is concerned, it deals with the Elements of the fabula in addition to the afterword that gives hints on "the use of narratology for cultural analysis". Under the umbrella term of structuralism, Bal gives sound to her model in this book. Besides, semantics was not absent from Bal’s discussions over the role of the constituents and their functions in the narrative. Thus, her model sounds more plausible and developed.